(untitled) (Journal of the Bangladesh Agricultural University, 2020)
The study was conducted for three months at the Faculty of Fisheries, Bangladesh Agricultural University to reveal the utilization of waste of as (Pangasianodon hypophthalamus) processing plants in the supplementary diets of tilapia fish (Oreochromis niloticus) in pond system to compare the growth performance of fishes with other two diets; one prepared in the laboratory with plant ingredients and another diet was purchased from market. In this study, feed formulated with pangas processing waste was named as Diet-2, feed formulated with plant source ingredients was named as Diet-3 while commercial feed which was purchased from market was named as Diet-1 and used as control Diet. These three diets were assigned to three treatments viz. T2, T3 and T1. Protein contents of diets were found 32.84%, 29.63% and 28.92% respectively. The water quality parameters (temperature, dissolved oxygen and pH) of the experimental ponds were monitored at 10 days of interval during the experimental period in different treatments. The results of the study showed that the weight increment for different treatments significantly varied and the highest weight gain in tilapia (175 ± 1.25 g) was found for Diet-2. The highest Specific Growth Rate (SGR; %/day) was 2.21% /day for Diet1. The Food Conversion Ratio (FCR) value obtained for Diet-2 (1.06) was lowest whereas Diet-3 (1.21) performed better than Diet-1 (1.16). The average protein efficiency ratio (PER) of Diet-2 (5.33) differed much compared to that of Diet-3 (5.21) and Diet-1 (5.56). The highest survival rate (%) of tilapia was 93.86%, found for Diet-2. The highest net production of tilapia was estimated 3879.2 kg/ha for Diet-2. To make the feed cost effective, inclusion of pangas processing waste along with other ingredients in tilapia diet (Diet-2) had a great significance. The calculated cost of each kilogram of Diet-2, Diet-3 and Diet-1 were 37.47 BDT, 42.10 BDT and 43.60 BDT, respectively. Based on the observation of present study, it could be recommended that, the waste materials from pangas processing plants can be better utilized as a source of protein in the diets of tilapia fish and at the same time it may contribute in reducing the environment pollution cased due to improper management of the fish industry. J Bangladesh Agril Univ 18(2): 516–523, 2020 https://doi.org/10.5455/JBAU.95923